Patologija malignih tumorjev dojke - Lamovec, Janez (Radiology and oncology (Ljubljana), 1998)
The morphological classification of breast tumors, in accordance to principlesof modern surgical pathology, provides the clinician not only with the basic data on the nature of tumor but also with important prognostic information. In the carcinoma of the breast, such information are as follows: lymph node status (positive or negative lymph nodes), grade of malignancy, size of the tumor and probably its histological type. The development of new technologies enabled the pathologist as well as the clinician to use numerous new tools and methods to determine a number of biochemical and molecular characteristics of the tumor. At this moment, however, the latter do not achieve the prognostic relevance of classical morphological features. Therefore, the pathologist should carefully folow the recommendatios and guidelines for handling and reporting surgical specimens since only by such means all morphological features giving most important prognostic information will be identified. In the article, some basic morphological methods, several important breast tumors, and a few biochemical and molecular methods in the diagnostics of breast cancer are discussed.
Keywords: Breast neoplasms; dojke; novotvorbe; Pathology; patologija; rak (medicina)